Hyperfiltration during early childhood precedes albuminuria in pediatric sickle cell nephropathy. Issue 4 (8th January 2019) - Lebensburger, Jeffrey D.; Aban, Inmaculada; Pernell, Brandi; Kasztan, Malgorzata; Feig, Daniel I.; Hilliard, Lee M.; Askenazi, David J.
Abstract: Background: In patients with diabetes mellitus, hyperfiltration precedes the development of albuminuria. Pediatric sickle cell anemia (SCA) patients have a high prevalence of hyperfiltration and albuminuria during early childhood and adolescence. We tested the hypothesis that hyperfiltration precedes the development of albuminuria in a longitudinal pediatric SCA cohort. Methods: We identified 91 participants with HbSS or SB0 thalassemia 5‐21 years of age enrolled in a longitudinal sickle cell nephropathy cohort study who had a cystatin C measured during early childhood (4‐10 years of age). Early hyperfiltration was defined as a mean eGFR >180 mL/min/1.73m 2 using cystatin C obtained from 4 to 10 years of age. Persistent albuminuria was defined as an albumin to creatinine ratio > 30 mg/g on two of three untimed urine specimens. Time to event analysis estimated survival curves for participants with and without hyperfiltration using Kaplan‐Meier curves and used logrank test for categorical variables to assess the association with time to development of the first episode persistent albuminuria. Results: Persistent albuminuria occurred more often and at an earlier age in participants with early hyperfiltration compared to those without early hyperfiltration (log‐rank, P = .004). Participants who developed albuminuria have a significant increase in their eGFR during childhood ( P = .003) as compared to participants who have not yet progressed to albuminuria ( P = .26). For every 1 g/dL increase in hemoglobin, the hazard ratio for developing persistent proteinuria decreased by 0.56 (95% CI: 0.3, 1.06, P = .07). Conclusion: Hyperfiltration precedes the development of persistent proteinuria in pediatric SCA patients. Intervention strategies should target lowering eGFR during early childhood.